Gamma Ray Induced Flower Colour and Seed Mutants in French Bean (Phaseolus vulgaris l.) - V. S. Kothekar, S. E. Mahamune and (Recent Research in Science and Technology, 2011)
Gamma ray doses of 0 (control),15,20 and 25 kR were applied to dormant seeds of Phaseolus vulgaris L. cv. Waghya. Mutations affecting flower colour and seed characteristics were detected in M2 generation. Highest mutation frequency for flower colour and seed characteristics were induced by 20 kR dose.Mutants with different flower colour and altered size, shape and coat colour of seeds were obtained.